It's hard to be the only girl: Obstacles facing adolescent girls in computer science contexts (Journal of The Colloquium for Information Systems Security Education, 2016)
Utilizing qualitative data gleaned from focus groups with adolescent girls attending computer science summer programs and competitions in cybersecurity (N=59, mean age = 16.3), this paper identifies psychological and institutional obstacles hindering girls in computer science contexts. Guided by ecological and social role theories, findings reveal psychological obstacles such as low feelings of confidence in the face of stereotype threat, low feelings of belonging due to experiences of exclusion in the classroom and perceptions of the computer science field as being masculine and isolating. Girls also reported low expectations from peers and teachers that discouraged their interest in pursuing computer science. Results have implications for educators, researchers and policy makers aiming to close gender gaps in the field of computer science. This study is unique in its' emphasis on how subtle changes in the social context can diminish, or bolster, girls' interest and confidence in computing.
Keywords: Qualitative; Learning Environments; Gender; Cybersecurity; Adolescence